Love and the Dingo: Review of Deborah Bird Rose, Wild Dog Dreaming: Love and Extinction - Freeman, Carol (Humanimalia, 2012)
Deborah Bird Rose. Wild Dog Dreaming: Love and Extinction. Charlottesville and London: University of Virginia Press, 2011. 184 pp. $29.50 hc, $16.50 pb.